Preliminary investigation into subjective well-being, mental health, resilience, and spinal cord injury. (1st November 2013) - Migliorini, Christine; Callaway, Libby; New, Peter
<x xml:space="preserve">Abstract</x> Objectives To undertake a pilot investigation into whether individuals whose subjective well-being had returned to the normal homeostatic range after a spinal cord injury (SCI) may be more resilient and therefore, at less risk of emotional distress over time. To consider the relative stability of subjective well-being in individuals with chronic SCI whose subjective well-being had previously returned to the normative homeostatic range. Study design Longitudinal study: Time 1 (T1) 2004 and Time 2 (T2) 2009. Setting Victoria, Australia. Participants Participants were adults living in the community with chronic SCI, who had no mental ill-health symptoms at T1. Outcome measures Scales include: Comprehensive Quality of Life Scale - Adult v5 (COMQoL-A5) at T1, Personal Well-being Index (PWI - the successor to the COMQol-A5) at T2, and Depression, Anxiety & Stress Scale - short form (DASS-21) at T1 and T2. Results Twenty-one adults participated at T1 and T2. Subjective well-being was stable for 57% of the cohort. However, 19% presented with symptoms of emotional distress by T2. There was no significant difference in age (P = 0.94) or time since injury (P = 0.51) between those reporting significant emotional symptoms and those without; nor was there any systematic change in health status. Conclusion This study yielded two important findings. First, individuals with chronic SCI may be vulnerable to mental health issues even after they have previously exhibited good resilience. Second, subjective well-being after SCI may not be as stable as suggested by the general quality of life literature that have examined genetic and personality connections to subjective well-being.